Facilitated Making in Museum‐Based Educational Makerspaces. (8th March 2021) - White, Annie M.; Akiva, Thomas; Wardrip, Peter S.; Brahms, Lisa
Abstract: The Maker Movement is on the rise and research shows that the ways educators facilitate making activities is a key element of supporting children's learning and development in this setting. As a field, we need to better understand how educators and children interact in makerspaces and the context that surrounds facilitation. In this study, we describe a research‐practice partnership between 11 museum educators and 4 researchers. Over two years, participants met to reflect on videos of educator‐child interactions and engage in dialog, reflective activities, and interviews around the topic of facilitation. Our collaboration resulted in a Model of Facilitated Making that categorizes types of facilitation moves, describes environmental influences on facilitation, and offers a process for considering techniques educators may use to facilitate. This model offers a framework for reflecting on facilitation in makerspaces, which has implications for practice and future research.